The ecology of suweg (Amorphophallus paeoniifolius) in the Citanduy and Cimanuk Watersheds, West Java, Indonesia - ASEP ZAINAL MUTAQIN; TEGUH HUSODO; DWI RUSTAM KENDARTO; INDRI WULANDARI; SYA SYA SHANIDA; ERRI NOVIAR MEGANTARA; DENNY KURNIADIE; JOHAN ISKANDAR; MOHAMAD NURZAMAN (Society for Indonesian Biodiversity, 2022)
Abstract. Mutaqin AZ, Husodo T, Kendarto DR, Wulandari I, Shanida SS, Megantara EN, Kurniadie D, Iskandar J, Nurzaman M. 2022. The ecology of suweg (Amorphophallus paeoniifolius) in the Citanduy and Cimanuk Watershed, West Java, Indonesia. Biodiversitas 23: 6520-6529. Suweg (Amorphophallus paeoniifolius (Dennst.) Nicolson) is one of the plants distributed in Indonesia, including in the Citanduy and Cimanuk Watershed. Amorphophallus grows in various land cover types. This species exhibits wide agroecological adaptation to dry and moist lands. Citanduy Watershed passes through the Leuwikeris Dam, and the Cimanuk watershed passes through the Kertajati International Airport. These projects can affect the condition of the surrounding environment, including biodiversity. This study was conducted to observe the distribution, population, and habitat characteristics of the suweg in the Citanduy and Cimanuk watersheds. Exploratory surveys and intensive studies were applied in this study. An exploratory survey was conducted randomly through direct observation. An intensive study was carried out to determine the ecological description of suweg in several areas, namely Kuta Subvillage, Ciangir Subvillage, and Pasiripis Village, with existing projects, still have strong local cultures, and the discovery of suweg growing. Suweg is growing in several sites, including the Citanduy and Cimanuk Watersheds, with certain elevations and environmental conditions. The Summed Dominant Ratio (SDR) of suweg in Kuta Subvillage, Ciangir Subvillage, and Pasiripis Village in the home garden and garden, respectively, are 8.50 and 13.77; 10.07 and 19.25; and 0 and 22.92, which indicate the population or density of suweg is low. The abiotic and biotic environmental parameters observed at each site varied.